Two new species of Colombian Epigomphus (Odonata: Gomphidae) - Bota-Sierra, Cornelio Andrés; Novelo-Gutiérrez, Rodolfo (Zootaxa, 2020)
The Neotropical genus Epigomphus Hagen in Selys, 1854 groups 31 species distributed from Mexico to northern Argentina. Only two species have been recorded so far from Colombia. Here we present two new species found in the north of the Andean Colombian Cordillera Central, Epigomphus rufus sp. nov. and Epigomphus brillantina sp. nov. Full descriptions of adult male and female and adult male respectively, plus diagnoses, pictures of the diagnostic characteristics, natural history notes, and a distribution map are provided.